Risk governance as a line of defense: Systematic review of hotspots for future research - John Agyekum Addae; Jorge Mota; António C. Moreira (Cogent Business & Management, 2023)
To forestall future financial crises, risk governance has been embraced as a line of defense. Therefore, this paper seeks to synthesize the risk governance literature, identifying gaps, and suggesting direction for future research, through a systematic literature review (SLR). Analyzing 151 papers from the Scopus and Web of Science databases, this paper finds a steady increase in academic work on risk governance. Using the theory, context, characteristics, and methodology (TCCM) framework, the study emphasizes the importance of chief risk officers, geographical context coverage, and effectiveness and regulation of risk governance. Methodologically, endogeneity issues are a major concern for researchers, agency theory (AT) being the most popular theory used. Finally, moderating and mediating variables that affect risk governance are identified as important but under-explored. While providing practitioners and policymakers with a framework, empirical testing is encouraged. The study contributes to SDG Goal 8, Target 10 of strengthening financial institutions and promoting a resilient financial system.
Keywords: 650; chief risk officer; enterprise risk management; risk committee; Risk governance; risk taking; TCCM framework